Anatomy of vector-like top-quark models in the alignment limit of the 2-Higgs Doublet Model Type-II - A. Arhrib; R. Benbrik; M. Boukidi; B. Manaut; S. Moretti (European Physical Journal C: Particles and Fields)
Abstract A comprehensive extension of the ordinary 2-Higgs Doublet Model (2HDM), supplemented by vector-like quarks (VLQs), in the “alignment limit” is presented. In such a scenario, we study the possibility that large hadron collider (LHC) searches for VLQs can profile their nature too, i.e., whether they belong to a singlet, doublet, or triplet representation. To achieve this, we exploit both standard model (SM) decays of VLQs with top-(anti)quark electromagnetic (EM) charge (T), i.e., into b, t quarks and $$W^± , Z,h$$ W ± , Z , h bosons (which turn out to be suppressed and hence T states can escape existing limits) as well as their exotic decays, i.e., into b, t (and possibly B) quarks and $$H^± , H, A$$ H ± , H , A bosons. We show that quite specific decay patterns emerge in the different VLQ representations so that, depending upon which T signals are accessed at the LHC, one may be able to ascertain the underlying beyond standard model (BSM) structure, especially if mass knowledge of the new fermionic and bosonic sectors can be inferred from (other) data.